Time-lapse graphical representation methods for mapping of Intermittent Rivers and Ephemeral Streams (IRES) - Maria-Danae STAMATAKI (European Journal of Geography)
Flow data visualizations describe runoff, flooding or drought, showing the interconnectivity and complexity of water data issues or water management problems. Intermittent Flow Rivers constitute more than half of the length of the global river network and their presence is expanding in response to climate change. A new approach is developed to visualize the flow of the Intermittent Rivers and Ephemeral Streams (IRES) based on the creation of time-lapse videos. Two statistical methods, the Natural Breaks and Equal Interval one, are used and evaluated for the creation of the mapping content. The flow dataset of IRES for the island of Crete (in Greece) is used as a case study for a six-year period. The results of both methods are used as an input to create the time-lapse videos of IRES. The videos show the flow fluctuation and cessation during a six-year period and the differences between the two methods.